Strategi Guru Bimbingan dan Konseling dalam Menerapkan Teknik Restrukturisasi Kognitif Untuk Meningkatkan Reseliensi Siswa - Siregar, Ehdatul Puadi; F, Firman; Rahman, Mohd Nazri Abdul; N, Netrawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Adolescence is often characterized by various challenges and obstacles that can have a negative impact. In an increasingly complex educational context, resilience or the ability to bounce back and adapt to change becomes very important for students. Guidance and counseling teachers play an important role in helping students develop this resilience. One strategy that can be used is cognitive restructuring techniques, which aim to change negative thought patterns into more positive and adaptive ones. By applying this technique, students can better overcome feelings of hopelessness, anxiety, and inability to face problems. This article provides insight and guidance for guidance and counseling teachers in implementing cognitive restructuring techniques to increase student resilience.